2020
DOI: 10.1002/art.41408
|View full text |Cite
|
Sign up to set email alerts
|

Do Smoking and Socioeconomic Factors Influence Imaging Outcomes in Axial Spondyloarthritis? Five‐Year Data From the DESIR Cohort

Abstract: Objective To investigate the relationship between smoking and imaging outcomes over 5 years in axial spondyloarthritis (SpA) and to assess whether socioeconomic factors influence these relationships. Methods Axial SpA patients from the Devenir des Spondylarthropathies Indifferérenciées Récentes cohort were included. The following 4 imaging outcomes were assessed by 3 central readers at baseline, 2 years, and 5 years: spine radiographs (using the modified Stoke Ankylosing Spondylitis Spine Score [mSASSS]), sacr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 27 publications
1
9
2
Order By: Relevance
“…There have been several studies about work participation in people with RMDs, including studies of interventions aiming to keep people in work 102. While there are some inconsistencies between these studies, perhaps due to power and different outcome assessments, many indicated that work was probably not detrimental (although there is evidence that physically demanding jobs are associated with increased radiographic progression in axSpA103 104) and in some cases beneficial for people with RMDs in terms of RMD outcomes 105–107. Given this, and the benefits of work on quality of life seen in the general population,108 work should receive increased attention in healthcare consultations with people with RMDs, and specialised health professionals should be involved.…”
Section: Resultsmentioning
confidence: 99%
“…There have been several studies about work participation in people with RMDs, including studies of interventions aiming to keep people in work 102. While there are some inconsistencies between these studies, perhaps due to power and different outcome assessments, many indicated that work was probably not detrimental (although there is evidence that physically demanding jobs are associated with increased radiographic progression in axSpA103 104) and in some cases beneficial for people with RMDs in terms of RMD outcomes 105–107. Given this, and the benefits of work on quality of life seen in the general population,108 work should receive increased attention in healthcare consultations with people with RMDs, and specialised health professionals should be involved.…”
Section: Resultsmentioning
confidence: 99%
“…In line with this observation, in previous analyses in DESIR we have seen smoking to be associated with MRI-SIJ inflammation specifically in patients with bluecollar jobs or low education. 26 The retention of smoking in the models may have contributed for clinical variables like function and spinal mobility, not having an independent significant effect in the multivariable models, corrected for the above-mentioned socioeconomic factors, while they were significant in univariable analyses. Disentangling individual effects especially when it comes to complex relationships between disease, context and outcome can thus be challenging partly due to residual confounding which cannot always be controlled.…”
Section: Spondyloarthritis Spondyloarthritis Spondyloarthritismentioning
confidence: 90%
“…17 In our study, education and in particular, lower education was associated with a higher hazard of SL. This observation could be explained by residual confounding, whereby people with lower education are more likely to take manual jobs, 26 which have further been shown to associate with poorer work outcome. Of note, a crosssectional multicentre study showed that mastery, an important personal factor linked to self-efficacy, was associated with being employed in patients, but only in those with low education.…”
Section: Spondyloarthritis Spondyloarthritis Spondyloarthritismentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, when measured with the ASDAS-CRP, disease activity did not differ between men and women [ 40 , 41 ]. Furthermore, although a link between smoking, inflammation and structural damage in early stages of axSpA has been suggested [ 21 , 42 ], the effect of smoking on long-term remission is not clear, and several studies have failed to find this association for all patients (association only in men and blue-collar patients) [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%